Morphometric Characterization and Haemato-biochemical Profile of Indian Fruit Bats - Dave, K. M.; Raval, S. K.; Rao, Neha; Nayak, J. B.; Kanani, A. N.; Patel, Beena; Panchal, M. T.; Patel, P. V. (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during January–December, 2022 at the Department of Veterinary Medicine, College of Veterinary Science & A.H., Kamdhenu University, Anand, Gujarat, India to study the normal values of haematological and biochemical parameters in both males and females of P. giganteus and C. spinx. In the study period, samples were collected from different district of Gujarat viz., Ahmedabad, Navsari and Valsad. In which two species of the fruit bats, P. gigantus (n=4) and C.sphinx (n=10) were screened for the morphometric identification. Based on morphometry both the species were identified. The haematology was performed in 27 fruit bats (Pteropus giganteus, n=13; Cynopterus sphinx, n=14) and biochemical analysis was carried out in 28 fruit bats (Pteropus giganteus, n=16; Cynopterus sphinx, n=12). In haematology, mean Hb, PCV and TLC were observed higher in P. gigantus than C.sphinx, whereas the value of TEC was lower. Between the species and sexes, hemoglobin and packed cell volume (PCV) values were comparatively equal, indicating similar oxygen-carrying capacity. In serum biochemistry, mean value of Creatinine, ALT, Total protein and BUN was observed higher in P. gigantus, whereas the AST was found high in C.sphinx. In comparison between male and female, the higher value of Creatinine and Total protein were found in male, whereas ALT, AST and BUN was found higher in female.